2023
DOI: 10.1371/journal.pone.0286468
|View full text |Cite
|
Sign up to set email alerts
|

Parent and early childhood educator perspectives of unstructured nature play for young children: A qualitative descriptive study

Abstract: Nature play is growing in popularity, with many early childhood settings transforming their outdoor play environments to incorporate more natural elements. Current research highlights the benefits of engaging in unstructured nature play for children’s health and development; yet little is known about the experiences of key nature play end-users such as parents and early childhood educators, even though they directly impact the application of nature play within early childhood settings. This study aimed to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…This study applied a qualitative descriptive (QD) research design to explore patient perceptions of factors that lead to their LEA [17]. QD methodology has previously been used in other qualitative research to gain perspectives of population groups about cultural and clinical factors [18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…This study applied a qualitative descriptive (QD) research design to explore patient perceptions of factors that lead to their LEA [17]. QD methodology has previously been used in other qualitative research to gain perspectives of population groups about cultural and clinical factors [18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…The recent national quality standard analysis conducted by ACECQA (2023) revealed that 97% of Australian ECE services are meeting the Quality Area 3 requirements (p. 17). Such access is seen as integral to the daily learning, play and developmental experiences for children (Dankiw et al, 2023;Hughes et al, 2022;Little, 2017).…”
Section: Outdoor Learning Provision In Early Childhood Education In A...mentioning
confidence: 99%